Congenital Resistance to Activated Protein C in Patients with Lupus Anticoagulants: Evaluation of Two Functional Assays - Galli, Monica; Duca, Francesca; Ruggeri, Luisa; Finazzi, Guido; Negri, Barbara; Moia, Marco (Thrombosis and Haemostasis, 1998)
The R506Q mutation (“Factor V Leiden”) is responsible for the resistance to activated Protein C (aPCR), that is evaluated by coagulation tests. Such tests cannot be used in patients with lupus anticoagulants (LAs), due to the interfering effect exerted by these antibodies on “in vitro” phospholipid-dependent coagulation tests. For this reason, assays have been developed to evaluate aPCR that are insensitive to the presence of LA antibodies. We evaluated two such coagulation tests in the plasma of 82 consecutive patients with LAs. By polymerase chain reaction 3 patients (3.6%) were found heterozygous for the R506Q mutation. aPCR was evaluated by two clotting assays, proposed to be “insensitive” to the presence of LAs: 1. aPCR-tissue factor-based assay, using Factor V deficient plasma and 1:40 diluted test plasma; 2. aPCR-dRVVT-based assay with highly concentrated phospholipids. Their interassay coefficient of variation was 28% and 6.2%, respectively. Compared to the polymerase chain reaction analysis, the 2 tests displayed the following characteristics: sensitivity 67% vs 100%, specificity 92% vs 96%, positive predictive value 25% vs 50%, negative predictive value 99% vs 100%, respectively. Among LA patients without the R506Q mutation, 5 scored positive in the aPCR-tissue factor-based assay, 2 in the aPCR-dRVVT-based assay and another one in both assays. Our findings suggest that the aPCRdRVVT-based test is more reliable and sensitive than the aPCR-tissue factor-based one to the R506Q mutation in patients with LAs. Both assays, when negative, make unlikely the presence of the R506Q mutation. Polymerase chain reaction analysis remains, however, to be performed when either test is positive.